APLIKASI ZOOM MEETING DALAM PEMBELAJARAN DARING UNTUK SEKOLAH DASAR PADA MASA COVID-19 DI PALEMBANG - Triwulandari, Rohmi; Prastowo, Andi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
The use of zoom meetings in theethics of the Covid-19 pandemic are some of the alternatives used during online learning. This article provides an overview of the application of zoom-based online learning during the Covid-19 pandemic hammering the Zoom Meeting application at Fathonah Integrated Islamic Elementary School Palembang grade III. This zoom-based learning is pursued in each subject both in practical activities and other learning processes carried out by the teacher during the learning process. The research method used in this study is a qualitative method of case study design through triangulation data collection techniques such as interviews, observations and documentation using Miles and Huberman data analysis methods is the process of data collection, data reduction, data presentation and verification / conclusion drawing. The results of the analysis of this study are that the existence of online learning activities through the zoom meeting application aims to achieve maximum learning activities for distance learning during the pandemic, but in the implementation of the learning process using the zoom application, it cannot be fully applied optimally to students in grade III at fathonah Integrated Islamic Elementary School Palembang.